Grounding the economic selection index for evaluation and selection of dairy cattle - S. Ruban; V. Danshyn; M. Matvieiev; I. Lastovska; O. O. Borshch; O. V. Borshch; V. Bilkevych; M. Fedorchenko; V. Lykhach (Diponegoro University, 2023)
The aim of the research was to develop a selection index for the evaluation and selection of dairy cattle for increasing milk production and reproductive traits. Materials of the research were data on milk production and reproduction of cows of the Ukrainian Black-and-White dairy breed in commercial farm in Kharkiv region. Studies showed that there was a certain antagonism between milk productivity and reproduction of the Ukrainian Black-and-White dairy cow. The coefficients of phenotypic correlation between milk yield, fat and protein yield and the days open ranged from +0.284 to +0.293. Selection indexes were built, which included protein, fat yield, and days open. The developed selection indexes were characterized by a high relationship with the protein yield (α<0.001), much lower – with the fat yield (α<0.05), while the relationship of the selection indexes with the days open was almost absent. The calculated estimates of correlation and regression coefficients made possible to predict correlated responses of milk production and reproduction traits on selection index. The results showed that the developed selection indexes allow increase the milk production of cows and at the same time to prevent decrease in the level of reproduction.